(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Food industry is dynamic industry as it depends highly on consumer interest and timing. Big Data Analytics can bring considerable revolution in food industry. It can be used to improve operational efficiency, timely delivery and also it can be used to personalize customer experience. In the field of marketing, Big Data Analytics helps in deciding pricing, demand forecasting as well as product promotion. The objective here is to show how Map Reduce technique can be used to process and analyze Big Data to extract useful information. This paper gives insight into use of Big Data Analytics in food marketing by analyzing huge amount of data using Big Data processing tool Apache Hadoop.